PT. Bank Rakyat Indonesia Tbk CSR Strategy “BRILian Fight Covid” in facing challenges in pandemic - fatonah, Nur Fatonah (COMMICAST, 2022)
The problem being studied in this research is the challenge of Corporate Social Responsibility. This form of social and environmental responsibility has been regulated in a law that serves as a guideline in carrying out CSR. Basically all companies are required and obliged to carry out some form of responsibility even during the pandemic. For example, in the industrial economic sector, most of which experienced a shift in value. One company that continues to maximize its CSR program is PT Bank Rakyat Indonesia, Tbk. The pandemic is a challenge for PT Bank Rakyat Indonesia, Tbk to continue implementing CSR programs through BRILIan Fight Covid. This program is a form of volunteer donation from BRI employees to collect funds which will later be donated to areas affected by the COVID-19 outbreak. The method used in this study uses the literature study method. The results of this study indicate a change in the priority of the CSR program implemented by PT Bank Rakyat Indonesia, Tbk, namely the BRI Peduli program. Some of the activities in it have changed by prioritizing the prevention and handling of Covid-19, such as Indonesia Cares, Prosperous Indonesia, Healthy Indonesia, and Indonesia Develops. Meanwhile, for the Indonesia Lestari, Smart Indonesia, Indonesia Takwa programs, the implementation is almost the same as before Covid-19, but is carried out by complying with health protocols. BRI has also added a new CSR program, namely BRILian Fight Covid-19 which is specifically for the handling and prevention of Covid-19. The research method regarding the CSR challenges carried out by PT Bank Rakyat Indonesia, Tbk during the pandemic was carried out using the literature study method. This literature method is carried out to adjust the data or theory with the facts in the field through library references such as books, articles, and journals related to the topic of discussion. The results of this study indicate that there is a level of community satisfaction with the BRILIan Fight Covid program carried out by PT. Bank Rakyat Indonesia, Tbk. Therefore, this research can provide benefits for the company to be used as the basis for analyzing the BRILIan Fight Covid program.